2002
DOI: 10.1017/s0305000902005111
|View full text |Cite
|
Sign up to set email alerts
|

Developing linguistic literacy: a comprehensive model

Abstract: This is a position paper modelling the domain of linguistic literacy and its development through the life span. It aims to provide a framework for the analysis of language development in the school years, integrating sociolinguistic and psycholinguistic notions of variation, language awareness, and literacy in a comprehensive model. The paper focuses on those aspects of literacy competence that are expressed in language as well as aspects of linguistic knowledge that are affected by literacy competence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
2
28

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(231 citation statements)
references
References 55 publications
5
196
2
28
Order By: Relevance
“…As their writing matures they begin to use a more sophisticated writing style when they gain more cognitive control over the written form. As this control develops children are more able to detach their written output from their spoken output and to "access non-default, less productive marked options" (Ravid & Tolchinsky, 2002). The data from the current study suggest that the normal-hearing group has begun to undergo this "detachment" while the cochlear implant group has not, thus they continue to use their spoken language scripts for writing.…”
Section: Discussionmentioning
confidence: 66%
“…As their writing matures they begin to use a more sophisticated writing style when they gain more cognitive control over the written form. As this control develops children are more able to detach their written output from their spoken output and to "access non-default, less productive marked options" (Ravid & Tolchinsky, 2002). The data from the current study suggest that the normal-hearing group has begun to undergo this "detachment" while the cochlear implant group has not, thus they continue to use their spoken language scripts for writing.…”
Section: Discussionmentioning
confidence: 66%
“…Many words from Coxhead's (2000) Academic Word List are already accessible to young learners. At a much younger age than previously thought, youngsters are sensitive to informational genres and register (Ravid & Tolchinsky, 2002).…”
Section: Resultsmentioning
confidence: 81%
“…For instance, research with Hebrew-speaking children and adults has shown that whereas knowledge of formal sophisticated morphology and syntax increases from age five to age seven, only college-educated adults and some older adolescents are capable of appropriately displaying this knowledge in the construction of texts (Ravid & Tolchinsky, 2002). As stated by Berman (2004) and by Ravid and Tolchinsky (2002), a crucial aspect of later language development, in addition to vocabulary expansion, is learning a variety of sophisticated morpho-syntactic structures and how to use them flexibly for diverse communicative purposes.…”
Section: Academic Language: a Research Agendamentioning
confidence: 99%
“…We might hypothesize that sociolinguistic awareness is a prerequisite to mastering academic language. Systematic linguistic variation can be dialectal, sociolectal, ethnic, or gender-based, as well as determined by genre, register, and modality (Ravid & Tolchinsky, 2002). The ability to switch appropriately across language varieties and registers depends on the opportunities to participate in various communicative situations (Hymes, 1974).…”
Section: What Is the Role Of Metapragmatic Awareness?mentioning
confidence: 99%